Effects of near-surface thawing on elastic properties and signatures of seismic surface waves - Svendsmark, Julie (The University of Bergen, 2023)
The ongoing temperature rise in the Arctic may have severe effects on large areas of today’s permanently frozen ground. Therefore, it is important to establish robust systems that can monitor permafrost changes with time. Surface wave methods are useful for mapping seismic structures in permafrost because they do not require abrupt velocity contrasts or normal velocity gradients (i.e., increasing velocity with depth). Rock physics models can be used to calculate how the stiffness and density of permafrost change with the degree of freezing, and they can be helpful when interpreting real seismic data from repeated acquisitions. I have tested several rock physics models and parameters of layered subsurface models to investigate their effects on elastic properties and surface wave propagation in permafrost. Changes in the dispersion characteristic of Rayleigh waves can be seen in the frequency-velocity spectra of the waves and depend on the distribution of the layer velocities and thicknesses. The seismic velocities depend on the ice saturation and the geometrical ice distribution in the pore space. However, other factors such as pore saturation, porosity, and sand properties also affect the seismic velocities and must be considered in analyses. Masteroppgave i geovitenskap GEOV399 MAMN-GEOV